PROBLEM-BASED MATHEMATICS TEACHING KITS INTEGRATED WITH ICT TO IMPROVE STUDENTS’ CRITICAL THINKING ABILITY IN JUNIOR HIGH SCHOOLS IN MEDAN - Waminton Rajagukguk; Erlinawaty Simanjuntak (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstract: This study was aimed to develop a set of integrated problem-based mathematics teaching kits implemented with ICT to improve the critical thinking ability of junior high school students. The study used 4-D learning device development model (define, design, develop, disseminate). The data were collected through the observation of the learning process and students' activity, students' questionnaire responses, and a critical thinking ability test. The findings showed that mathematics teaching materials consisting of teaching kits as a teachers’ handbook based on ICT integrated problem-based materials completed with lesson plans, worksheets, and the use of media learning were appropriate to use.Based on the test results conducted in the field, the teaching kits can enhance the students' critical thinking ability. The findings showed that the average gain in two schools was in the range of g 0.7, which means that the students' critical thinking ability belonged to the high category, while that of the third school was in the range of 0.3  g  0.7 at 0.62 which means the students’ critical thinking ability belonged to the fair category. Keywords: learning device, information communication technology (ICT), critical thinking PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS MASALAH TERINTEGRASI ICT UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP KOTA MEDAN Abstrak: Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran matematika berbasis masalah terintegrasi dengan ICT untuk meningkatkan kemampuan berpikir kritis siswa SMP. Penelitian menggunakan model pengembangan perangkat pembelajaran model 4-D (define, design, develop, disseminate). Data penelitian diperoleh melalui pengamatan proses pembelajaran dan aktivitas siswa, angket respon siswa, dan tes kemampuan berpikir kritis. Hasil penelitian menunjukkan bahwa perangkat pembelajaran yang terdiri atas bahan ajar matematika sebagai buku pegangan guru berbasis masalah yang terintegrasi dengan ICT disertai RPP, LKS, dan media pembelajaran layak digunakan. Berdasarkan hasil uji coba di lapangan, perangkat pembelajaran tersebut dapat meningkatkan kemampuan berpikir kritis siswa. Hasil penelitian menunjukkan bahwa rata-rata gain pada dua sekolah dimana sekolah pertama dan kedua didapat rentang g 0,7 yang artinya kemampuan berpikir kritis siswa pada kategori tinggi, sedangkan pada sekolah yang ketiga rentang 0,3  g  0,7 yaitu 0,62 yang artinya kemampuan berpikir kritis siswa mengalami peningkatan pada kategori sedang. Kata Kunci: perangkat pembelajaran, ICT, berpikir kritis